The degree of social and educational integration and absorption of Arab Bedouin female students in teacher training institutions in Israel - Abu-Ajaj, Abraheem (Kultura-Społeczeństwo-Edukacja, 2018)
The issue of the process of integration and absorption of Arab Bedouin female students in teacher training institutions in Israel constitutes a significant yet critical chapter in the course of forming the personal and professional identity of the prospective teacher. The main purpose of this article is to describe the difficulties experienced by Arab Bedouin female students during the process of their social and educational integration and absorption in teacher training institutions. Also, to deal with the differences between Arab and Jewish teacher training institutions. Furthermore, to what extent the cultural encounter is perceived by the students that would enable them to have social and educational integration. The study involved 200 Bedouin Arab female students living in the Negev and learning in four teacher-training colleges in Israel; Kaye College of Education, Achva College, Sakhnin College for teacher training and Al-Qasmi College. The students answered a questionnaire that was written for this study. The findings of the study indicated many difficulties in the process of absorbing and integrating Arab Bedouin students in various teacher-training institutions in the country. Not to mention, language difficulties experienced by them with regard to reading articles and writing papers, not in their native tongue. The multicultural encounter between the different genders also poses a great difficulty in addition to the age difference between Arab and Jewish students. Furthermore, the policy of the Israeli academic institutions does not fully represent the Arab culture and in the interaction between the academic and administrative staff and the Arab Bedouin students.